Unlocking sustainable agricultural development in Africa via bio-nanofertilizer application - challenges, opportunities and prospects - Adewale T. Irewale; Christian O. Dimkpa; Foluso O. Agunbiade; Oyeboade A. Oyetunde; Elias E. Elemike; Emeka E. Oguzie (Scientific African, 2024)
A combination of rapid population growth, climate change, and environmental degradation have placed immense pressure on global food sources and increased food security concerns especially in developing economies like those of African countries. Notably, efforts to produce food for the rising human population have continued to burden arable lands across the globe, necessitating heavy use of chemical fertilizers to increase crop yield. While the widespread use of conventional fertilizers has indeed enhanced crop productivity, its sustainability is threatened by rapid soil degradation and rising environmental concerns resulting from chemical compound accumulation across several ecosystems. The invention of nanotechnology, which is the synthesis and manipulation of materials at the nanometer (1 to 100 nm) range, promises potential solutions to these agricultural sustainability challenges. Specifically, theoretical, and experimental research on nanofertilizers have highlighted significant potential for their employment in sustainable farming practices. The current review examines the benefits conferred by the delivery of nutrients to plants at the nanoscale, outlining the progress, challenges, and opportunities for adopting this emerging technology by African countries, and highlighting future perspectives and areas of possible collaborations globally.